Escherichia coli and Pseudomonas aeruginosa Isolated From Urine of Healthy Bovine Have Potential as Emerging Human and Bovine Pathogens - Giannattasio-Ferraz, Silvia; Ene, Adriana; Gomes, Vitor Júnio; Queiroz, Cid Oliveira; Maskeri, Laura; Oliveira, André Penido; Putonti, Catherine; Barbosa-Stancioli, Edel F. (Frontiers in Microbiology, 2022)
The study of livestock microbiota has immediate benefits for animal health as well as mitigating food contamination and emerging pathogens. While prior research has indicated the gastrointestinal tract of cattle as the source for many zoonoses, including Shiga-toxin producing Escherichia coli and antibiotic resistant bacteria, the bovine urinary tract microbiota has yet to be thoroughly investigated. Here, we describe 5 E. coli and 4 Pseudomonas aeruginosa strains isolated from urine of dairy Gyr cattle. While both species are typically associated with including urinary tract infections and mastitis, all of the animals sampled were healthy. The bovine urinary strains were compared to E. coli and P. aeruginosa isolates from other bovine samples as well as human urinary samples. While the bovine urinary E. coli isolates had genomic similarity to isolates from the gastrointestinal tract of cattle and other agricultural animals, the bovine urinary P. aeruginosa strains were most similar to human isolates suggesting niche adaptation rather than host adaptation. Examination of prophages harbored by these bovine isolates revealed similarity with prophages within distantly related E. coli and P. aeruginosa isolates from the human urinary tract. This suggests that related urinary phages may persist and/or be shared between mammals. Future studies of the bovine urinary microbiota are needed to ascertain if E. coli and P. aeruginosa are resident members of this niche and/or possible sources for emerging pathogens in humans.